Self-adaptive migration NSGA and optimal design of inductors for magneto-fluid hyperthermia. Issue 4 (6th July 2018) - Sieni, Elisabetta; Di Barba, Paolo; Dughiero, Fabrizio; Forzan, Michele
Abstract : Purpose: The purpose of this paper is to present a modified version of the non-dominated sorted genetic algorithm with an application in the design optimization of a power inductor for magneto-fluid hyperthermia (MFH). Design/methodology/approach: The proposed evolutionary algorithm is a modified version of migration-non-dominated sorting genetic algorithms (M-NSGA) that now includes the self-adaption of migration events- non-dominated sorting genetic algorithms (SA-M-NSGA). Moreover, a criterion based on the evolution of the approximated Pareto front has been activated for the automatic stop of the computation. Numerical experiments have been based on both an analytical benchmark and a real-life case study; the latter, which deals with the design of a class of power inductors for tests of MFH, is characterized by finite element analysis of the magnetic field. Findings: The SA-M-NSGA substantially varies the genetic heritage of the population during the optimization process and allows for a faster convergence. Originality/value: The proposed SA-M-NSGA is able to find a wider Pareto front with a computational effort comparable to a standard NSGA-II implementation.